Engaging advertisements exploring native advertising in the socia media marketing strategy of the Davao City tourism Operation Office - Hidalgo, Fila guia G.
Engaging advertisements: exploring native advertising in the social media marketing strategy of the Davao Tourism Operations Office, explores and looks into the potentials of Native Advertising in the social media marketing of DCTOO in Facebook. It probes into the capability of using pictures in Facebook posts as native advertising for engagement. This is to address the difficulty of DCTOO to engage audiences because of using posters, a display advertising method. This research production was guided by the principles of native advertising and photography to see if it can engage its viewers as it aims to become a part of their experience in Facebook. Four tourism enterprises and subjects for the photographs were selected and caption that aims to stimulate engagement were created in the production process. The native ads were posted in Facebook and the hits were monitored within the month of December. The Facebook Posts Engagement Rate results show that compared to the non-native ads posted in December 2011 and 2012, there has been only a small increase in engagement seen in the native ads. Given these results, it can be said that native advertising has the capacity to engage its audience. The engagement was shown thru the number of likes, comments, and shares as these belong to a higher level of engagement. Moreover, it is proposed that native ads have the higher probability to engage its viewers if included I a comprehensive and sustained campaign as proven by many campaigns that used native advertising. In an advertising campaign, the native ads have more and longer opportunity to be exposed in a medium as these ads establish the image of the campaign and engage the audiences.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts